Comparison of intravenous ibuprofen and paracetamol for postoperative pain management after laparoscopic sleeve gastrectomy. A randomized controlled study - Çiftçi, Bahadır; Ekinci, Mürsel; Çelik, Erkan Cem; Kaçıroğlu, Ahmet; Karakaya, Muhammet Ahmet; Demiraran, Yavuz; Özdenkaya, Yaşar (Springer, 2019)
Background Laparoscopic sleeve gastrectomy (LSG) is defined as the first-step bariatric surgery for the treatment of obesity. Opioid analgesics are often preferred for pain management because of their strong analgesic potentials. However, opioids have undesirable adverse effects. Objectives The objective of this study is to evaluate and compare the influence of IV forms of ibuprofen and paracetamol on pain management and opioid consumption on patients undergoing LSG surgery. Setting This study was conducted at Istanbul Medipol University Hospital. Methods Patients were stratified into three groups. Group I (group ibuprofen, n = 30) was administered 800 mg of IV ibuprofen, group P (group paracetamol, n = 30) was administered 1000 mg of IV paracetamol, and group C (control group, n = 30) was given 100 ml of saline solution. We evaluated opioid consumption and VAS scores postoperatively. Results This study included 90 patients who underwent LSG. The use of rescue medication in group I was statistically lower than the other groups. VAS scores in group I and group P at recovery and at 2, 4, 8, 12, and 24 h were lower than those in group C. In particular, the VAS scores in group I at the first 2 h postoperatively were significantly lower than those in group P (p <0.05). Opioid consumption in group C was significantly higher than the other groups (p <0.05). Conclusion Our study suggested that IV ibuprofen resulted in lower pain scores compared to paracetamol by reducing postoperative opioid use in the first 24 h in patients undergoing LSG surgery.
WOS: 000462182400003
PubMed ID: 30474791
Keywords: Laparoscopic Sleeve Gastrectomy; Analgesia; Ibuprofeny